Probiotics and MicroRNA: Their Roles in the Host–Microbe Interactions - Zhao, Ying; Zeng, Yan; Zeng, Dong; Wang, Hesong; Zhou, Mengjia; Sun, Ning; Xin, Jinge; Khalique, Abdul; Rajput, Danish Sharafat; Pan, Kangcheng; Shu, Gang; Jing, Bo; et al. (Frontiers in Microbiology, 2021)
Probiotics are widely accepted to be beneficial for the maintenance of the gut homeostasis – the dynamic and healthy interactions between host and gut microorganisms. In addition, emerging as a key molecule of inter-domain communication, microRNAs (miRNAs) can also mediate the host–microbe interactions. However, a comprehensive description and summary of the association between miRNAs and probiotics have not been reported yet. In this review, we have discussed the roles of probiotics and miRNAs in host–microbe interactions and proposed the association of probiotics with altered miRNAs in various intestinal diseases and potential molecular mechanisms underlying the action of probiotics. Furthermore, we provided a perspective of probiotics–miRNA–host/gut microbiota axis applied in search of disease management highly associated with the gut microbiome, which will potentially prove to be beneficial for future studies.